1974
DOI: 10.1021/jo00927a003
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Benzodioxanes. I. Synthesis involving the reaction of .alpha.-halo Michael acceptors with catechol

Abstract: Halo Michael acceptors react with catechol in aprotic solvents in the presence of potassium carbonate to form 2-substituted 1,4-benzodioxanes. Cis 0-alkyl and 0-alicyclic -halo Michael acceptors yield primarily cis 2,3-disubstituted 1,4-benzodioxanes, whereas trans 2,3-disubstituted isomers predominate when catechol is treated with trans 0-alkyl -halo Michael acceptors. It is therefore inferred that the reaction proceeds via a cis Michael addition of catechol monoanion, followed by intramolecular nucleophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The mechanism of this reaction was abundantly studied few decades ago firstly by Koo and coworkers 21 and later by Caputo's research group. 22 They strengthened the hypothesis of the initial dehydrobromination of the 2,3-dibromopropionate, achieving the 2-bromoacrylate, and the consecutive Michael addition of the cathecol anion on the primary carbon. Similarly, considering this simple procedure, we decided to apply it on 1,2-mercaptophenol instead of catechol, treating the 2-hydroxythiophenol with methyl or ethyl 2,3-dibromopropionate, in presence of triethylamine (TEA) as weak organic base.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The mechanism of this reaction was abundantly studied few decades ago firstly by Koo and coworkers 21 and later by Caputo's research group. 22 They strengthened the hypothesis of the initial dehydrobromination of the 2,3-dibromopropionate, achieving the 2-bromoacrylate, and the consecutive Michael addition of the cathecol anion on the primary carbon. Similarly, considering this simple procedure, we decided to apply it on 1,2-mercaptophenol instead of catechol, treating the 2-hydroxythiophenol with methyl or ethyl 2,3-dibromopropionate, in presence of triethylamine (TEA) as weak organic base.…”
Section: Introductionmentioning
confidence: 75%
“…The mechanism of this reaction was abundantly studied a few decades ago, first by Koo and co-workers and later by Caputo’s research group . They strengthened the hypothesis of the initial dehydrobromination of the 2,3-dibromopropionate, achieving the 2-bromoacrylate, and the consecutive Michael addition of the cathecol anion on the primary carbon.…”
Section: Introductionmentioning
confidence: 98%
“…In the 1 H NMR spectrum, the coupling constant of H-β (7.9 Hz) suggested that the two methine protons could be in as a trans configuration. 50, 51 Proton signals of a hydroxymethylene moiety at δ 3.52 and 3.33 (H-γ) were observed, and one of them (δ 3.52) was long-range correlated with a methine carbon signal at δ 75.9 (C-β). These observations indicated the presence of a lignan moiety, and this was confirmed by a TOCSY experiment where proton signals H-2Љ, H-5Љ, and H-6Љ were correlated with H-α and H-β to become a network.…”
Section: Resultsmentioning
confidence: 99%
“…Found: C, 55.44; , 6.19; N, 5.00. meso-2,3,4,5,5a,lla-Hexahydro[l,4]benzodioxino [2,3-d]azepine (14). Crude N-methylsulfonyl [1,4]benzodioxinoazepine 13 (37.1 g, 0.131 mol) was dissolved in benzene (200 mL) and added during 15 min to a well-stirred solution of Red-al (Aldrich Chemical Co.) (191 mL of a 70% solution, 0.66 mol) in benzene (250 mL). The mixture was refluxed for 4 h and then allowed to stand overnight at room temperature.…”
Section: Experimental Section7mentioning
confidence: 99%